BUDIDAYA ITIK SEBAGAI PETELUR PADA KELOMPOK KARANG TARUNA DI DESA BORIKAMASE - Abna, Nurjannah; Syam, Netty (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2019)
Youth Organization (Karang Taruna) is a forum for the development of nonpartisan young people,who grow on the basis of awareness and sense of social responsibility from, by and for thecommunity, especially the younger generation in Borikamase Village, Kecamatan Maros Baru,Maros Regency. The youth organization is engaged in social welfare, helping to prepare youth inefforts to create jobs and the ability to manage businesses. Duck farming is one of the businessesthat are in demand in Borikamase Village. The location of the village is in the swamp area, so it isvery potential to cultivate laying ducks. In addition, the community's need for eggs is also veryhigh, as a source of protein. The objectives of the activity are (1) to form and developeconomically independent partners in Borikamase Village (2) The provision of training andcounseling in the form of youth management management theory. The results of the activityconcluded that this activity received a positive response from the training and mentoringparticipants reflected in the attendance response of Karang Taruna members in each meeting andtheir enthusiasm in participating in the competition held.